2000
DOI: 10.1103/physrevd.62.085005
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization group study of the Chern-Simons field coupled to scalar matter in a modified BPHZ subtraction scheme

Abstract: We apply a soft version of the BPHZ subtraction scheme to the computation of two-loop corrections from an Abelian Chern-Simons field coupled to (massive) scalar matter with a λ(Φ † Φ) 2 and ν(Φ † Φ) 3 self-interactions. The two-loop renormalization group functions are calculated. We compare our results with those in the literature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
(66 reference statements)
3
12
0
Order By: Relevance
“…confirming the results obtained in [5] by using soft BPHZ [4] and also in [7] by using dimensional reduction. These results are also in qualitative agreement with that of [8] but, differently of what happens with the effective potential, disagree with those of [14] (which in our notation are γ ϕ = 0 and β ν = 7 4π 2 ν 2 ) where dimensional regularization with minimal subtraction was used.…”
Section: Renormalization Group Analysissupporting
confidence: 86%
“…confirming the results obtained in [5] by using soft BPHZ [4] and also in [7] by using dimensional reduction. These results are also in qualitative agreement with that of [8] but, differently of what happens with the effective potential, disagree with those of [14] (which in our notation are γ ϕ = 0 and β ν = 7 4π 2 ν 2 ) where dimensional regularization with minimal subtraction was used.…”
Section: Renormalization Group Analysissupporting
confidence: 86%
“…Now, studying a possible minimum of such a Kählerian effective superpotential for v Þ 0, we found that e 2 % ð4:7 Â 10 À2 Þe 6 , which implies e $ 2. Thus, as in other four-and three-dimensional scalar models [1][2][3][4][5][6], in this case the Coleman-Weinberg effect is not feasible, because for N ¼ 2 the model presents only one coupling constant into play. Our results are in agreement with previous results obtained by Gaiotto and Yin [20] and Buchbinder et al [21,34], where it was shown that the N ¼ 2, 3 SCSM does not exhibit spontaneous breaking of superconformal invariance.…”
Section: Extended Susy Modelmentioning
confidence: 94%
“…The same happens in the supersymmetric Maxwell theory [17], and nonsupersymmetric three-dimensional gauge models [2][3][4][5][6]. Now, we evaluate the two-loop contributions to the tadpole equation, which arise from the diagrams depicted in Fig.…”
Section: The Supersymmetric D ¼ ð2 þ 1þ Chern-simons-matter Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…In this case, however, dynamical symmetry breaking appears only at two loops [17,18,19,20], and not at the one loop level, as in four dimensions.…”
mentioning
confidence: 87%